Stream‐Discharge Surges Generated by Groundwater Flow. Issue 13 (10th July 2019) - Guérin, Adrien; Devauchelle, Olivier; Robert, Vincent; Kitou, Thierry; Dessert, Céline; Quiquerez, Amélie; Allemand, Pascal; Lajeunesse, Eric
Abstract: Catchments respond to rainfall by storing and releasing water according to their internal dynamics. Groundwater had long been treated as the slow reservoir in this process, but isotopic measurements showed how responsive it can be. Here, we investigate the mechanics of groundwater's contribution to floods. To do so, we monitored over 3 years the shape of the water table in, and the runoff out of, a small tropical catchment. We find that groundwater and runoff respond within minutes of a rainfall event. Using an asymptotic theory inspired by recent laboratory experiments, we suggest that the peak water discharge at the catchment's outlet increases like the rainfall rate to the power of 3/2. This formula consistently predicts the stream's response to the 137 isolated rainfall events recorded during our field survey. In addition, its prefactor yields an estimate of the average groundwater storage. Plain Language Summary: Rainwater infiltrates into the ground, accumulates in porous rocks, and eventually flows toward a neighboring stream. Although this underground travel often takes millennia, groundwater can contribute quickly to floods. To understand how an underground flow can be so responsive, we have recorded the motion of the groundwater surface in a small tropical catchment during 3 years. We find that groundwater swells within minutes of a rain event and that this deformation directly pushes more water into the stream. The resulting stream‐discharge peak strengthens faster than the rainfall intensity: A threefold increase of the latter causes a fivefold increase of the stream discharge. Including this mechanism into flood‐forecasting models should allow us to better predict the impact of extreme precipitations. Finally, we introduce a method to measure how much water an aquifer stores during a rainfall event, before releasing it—a central parameter for the management of water resources. Key Points: High‐frequency measurements show that groundwater nonlinearly amplifies the response of a catchment to rainfall events The stormflow regime of the underground flow consistently predicts the peak runoff We propose a method to measure the volume of water available in a shallow aquifer based on the hydrograph of the corresponding catchment